Preferred choice of work setting among nurses in Thailand: A discrete choice experiment. (8th May 2014) - Kunaviktikul, Wipada; Chitpakdee, Bunpitcha; Srisuphan, Wichit; Bossert, Thomas
Abstract The shortage of health personnel and nurses is an important issue in many developed and developing countries. Understanding preferred choice of work setting is an important strategy for retaining nurses in their work. The purpose of this study was to determine choices made by nurses in Thailand relative to their preferences for a work setting. A discrete choice experiment was conducted to elicit attributes and levels of job characteristics expected to contribute to work‐place preferences. The sample included 921 nurses and was selected using stratified random sampling. A random effects probit model was used to identify factors contributing to work‐setting preferences. The results showed that nurses' first work‐place preference was a high level of work setting. The second preference was to work in a hospital in the same province as their families. The results provide information for hospital and nurse administrators and policymakers seeking to address the nursing shortage.